Mechanical properties of water hyacinth (Eichhornia crassipes) and sansevieria (Sansevieria trifasciata) fiber reinforced composite with polyester matric - Nurfajriani Nurfajriani; Ahmad Nasir Pulungan; Ajat Sudrajat; MS Manurung; Rahayu Rahayu (Jurnal Pendidikan Kimia, 2024)
Sansevieria (Sansevieria trifasciata) fibers and water hyacinth (Eichhornia Crassipes) fibers as natural fiber producers with good quality have good potential to be developed. This study aims to examine the production and characteristics of composites made from sansevieria fiber and water hyacinth fiber with a polyester matrix through the employment of the hand lay up method. This composite uses variations in the composition of the fiber mixture by soaking 5% NaOH for 2 hours at room temperature, for the resulting composite material. The resulting composite material is then subjected to a bending test to determine its mechanical properties, utilizing the ASTM D638 test standard. Based on the conducted research, the most favorable outcomes in terms of bending test results and modulus of elasticity are observed with a 10% incorporation of sansevieria fiber, yielding an average of 5.520 MPa for bending test and an elastic modulus of 7.444 MPa. Alternatively, when combining both fibers, the optimal mixture consists of 20% sansevieria fiber and 20% eceng gondok fiber, resulting in an average bending test value of 7.503 MPa and a modulus of elasticity of 7.873 MPa.